Perancangan Sistem Informasi Akuntansi Laporan Sisa Hasil Usaha Berbasis Web pada Koperasi Karyawan PT. Kahatex “Wiryatama” Cimahi - Azizah, Rizqi Nur; Karyadi; Kusumadiarti, Rini Suwartika (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This study aims to create an accounting information system design for web-based residual business results at the PT. KAHATEX "WIRYATAMA" Cimahi Employee Cooperative. This research uses qualitative methods. Data collection techniques are used by observation, interviews and . The software method used is the waterfall. From the research conducted, the authors found several problems including the savings and loan process and the calculation of remaining business results still using Microsoft Exel, so data processing takes a long time and the accuracy of reports is less accurate. Therefore, an information system is designed using data flow diagrams and implemented in the PHP and MYSQL programming languages as databases. As for some suggestions given to deal with existing problems, namely optimizing savings and loan information systems and residual business results using applications that have been designed, can develop existing systems and can maintain system to improve better performance.